Automated GMP Production and Preclinical Evaluation of [68Ga]Ga-TEoS-DAZA and [68Ga]Ga-TMoS-DAZA - Julia Greiser; Thomas Winkens; Olga Perkas; Christian Kuehnel; Wolfgang Weigand; Martin Freesmeyer (MDPI AG, 2022)
[68Ga]Ga-TEoS-DAZA and [68Ga]Ga-TMoS-DAZA are two novel radiotracers suitable for functional PET liver imaging. Due to their specific liver uptake and biliary excretion, the tracers may be applied for segmental liver function quantification, gall tree imaging and the differential diagnosis of liver nodules. The purpose of this study was to investigate problems that occurred initially during the development of the GMP compliant synthesis procedure and to evaluate the tracers in a preclinical model. After low radiolabeling yields were attributed to precursor instability at high temperatures, an optimized radiolabeling procedure was established. Quality controls were in accordance with Ph. Eur. requirements and gave compliant results, although the method for the determination of the 68Ga colloid is partially inhibited due to the presence of a radioactive by-product. The determination of logP revealed [68Ga]Ga-TEoS-DAZA (ethoxy bearing) to be more lipophilic than [68Ga]Ga-TMoS-DAZA (methoxy bearing). Accordingly, biodistribution studies in an in ovo model showed a higher liver uptake for [68Ga]Ga-TEoS-DAZA. In dynamic in ovo PET imaging, rapid tracer accumulation in the liver was observed. Similarly, the activity in the intestines rose steadily within the first hour p.i., indicating biliary excretion. As [68Ga]Ga-TEoS-DAZA and [68Ga]Ga-TMoS-DAZA can be prepared according to GMP guidelines, transition into the early clinical phase is now possible.